(untitled) (Global Journal of Human-Social Science, 2025)
The two books examined in this article highlight the complexities of identity issues in contemporary multicultural Spain The authors examine the dominant narratives surrounding otherness as they relate to black African immigrants highlighting the perspectives and assumptions held by white discourse The outcome decisively employs rhetorical strategies to construct a fictional immigrant through clear and distinct stereotypical portrayals Thus in Nativas by Inongo-vi-Makom the black man becomes a sex beast In V ctor Omgb s Calella sen sa da immigrants who are marginalized are placed on the edges of Spanish society reduced to a distorted image within a civilized community